Farmers' preferences on seed purchase timing - rice, cowpea, and maize growers in Nigeria - Takeshima, Hiroyuki; Nagarajan, Latha; Salau, Sheu; Oyekale, Abayomi (International Food Policy Research Institute, 2010)
The timely availability of seeds at planting time is considered one of the important factors for faster improved seed adoption in Nigeria. There is a lack of empirical information on how much more farmers are willing to pay (WTP) for seeds at planting time compared to a few months before planting time. The information on such WTP can help assess the feasibility of public sector support for the timely delivery of improved seeds. This study estimates how farmers' WTP for rice, cowpea and maize seeds varies depending on the purchase timing, using information on both farmers' observed purchase behaviors and their stated preferences. Results indicate that low-income farmers may prefer to pay higher prices for cowpea seeds if those seeds can be bought closer to planting season. Policy implications and future research needs are discussed.